(untitled) (The Review of Diabetic Studies, 2025)
Vision 2030 shift to value-based healthcare (VBHC) in Saudi Arabia is paradigm shift in volume-based care toward outcome-based care focusing on cost-efficiency, patient outcomes and equity. This systematic review is a synthesis of the literature published in 2020-2025 in the area of VBHC measures (e.g., patient-reported outcomes, cost per quality-adjusted life year), models (e.g., Model of Care, bundled payments), and integration of aspects of chronic disease management to primary (preventive screenings) and secondary (specialized interventions) care. Based on 42 studies, it can be found that there will be a gradual adoption (20% in 2020 to 60% in 2025 in urban clusters), enhanced CDM continuity (e.g., 30% reduction in hospital readmissions through integrated referrals), yet still there will be barriers to adoption such as data silos and rural disparities. Illustrations portray trends of adoption and outcome measures. The discussion presents criticism of implementation deficiencies, and the recommendations include the recommendation of standardized metrics, interoperability and interdisciplinary teams. Such a shift is in line with the Health Sector Transformation Program (HSTP) of Vision 2030, which offers lower rates of chronic diseases (e.g., diabetes rate of 18%).